Chromosomal instability in sporadic colorectal cancer - Łaczmańska, Izabela; Kozłowska, Joanna (Contemporary Oncology/Współczesna Onkologia, 2009)
Chromosomal instability together with microsatellite and epigenetic instability is a defined characteristic of a variety of human cancers. Studies on chromosomal instability are first line examinations that allow the location of critical regions or genes crucial for cancer development and progression. Sporadic colorectal cancer is one of the most common cancers in the world. According to its biology it can be divided into two groups: microsatellite instable and chromo-somal instable. Chromosomal instability is characteristic for about 85% of sporadic colorectal cancer; therefore a correlation between a pattern of chromosomal aberrations and histopathological as well as clinical features of colorectal cancer is widely investigated. Unbalanced aberrations can be found using the CGH technique without the step of cell culture. The presence of specific aberrations has been reported for colorectal cancer, which can be interpreted as the presence of a stable cancer genotype. This information may be useful for clinical therapy.